Evaluasi Program Literasi Membaca Sekolah Dasar di SD Negeri 1 Kedungjati Menggunakan Model Goal Free Evaluation - Nugroho, Christopher Dean Arfie; Mawardi, Mawardi (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – Based on a survey conducted by the Program for International Student Assessment (PISA) released in 2019, Indonesia is ranked 62nd out of 70 countries, placing it among the bottom 10 countries with low literacy levels. In response, the Indonesian government promoted the School Literacy Movement (GLS), a comprehensive initiative aimed at transforming schools into learning organizations where all members are literate for life, with the involvement of the community. The purpose of this study was to evaluate the reading literacy movement program at SD Negeri 1 Kedungjat.Method – This research employs a descriptive qualitative design. The study employs the Goal-Free Evaluation model, which enables researchers to evaluate the program without concentrating on its specific goals. Data collection techniques include document studies, observations, and interviews. Data analysis techniques used in this research follow the Miles and Huberman approach, which involves data collection, data reduction, data presentation, and conclusion drawing, with the data presented in descriptive text form.Findings – According to the study findings, the reading literacy movement involves instilling a 15-minute reading habit before commencing lessons. Supporting factors within this movement include a diverse range of reading materials, a conducive environment, and well-equipped libraries. The research indicates that the implementation of the reading literacy movement has been successful and has yielded positive outcomes, despite not being uniformly distributed across all classes. Research Implications – This study outlines the beneficial effects of the school literacy movement on students' reading interest, leading to an increased enthusiasm for reading. Furthermore, it demonstrates that the literacy movement enhances students' comprehension levels.